Modelling and optimisation of electromagnetically coupled solid manufacturing processes. (2018) - Bay, F.; Alves, J.; Barlier, J.
Electromagnetically-coupled manufacturing processes cover a wide range of applications - such as magnetic pulse forming processes or induction heat treatment processes. This paper presents a computational model and numerical tool developed in our laboratory for modelling these processes taking into account their specificities.